Doing relationships and sexuality education with young people in state care. (March 2017) - Hyde, Abbey; Fullerton, Deirdre; McKeown, Caroline; Lohan, Maria; Dunne, Laura; Macdonald, Geraldine
Background: Existing literature indicates that young people in state care have particular sexual health needs that include addressing their social and emotional well-being, yet little has been published as to how these components of sex education are actually delivered by service-providers. Objective: The aim of this study was to analyse the processes involved in delivering relationship and sexuality education to young people in state care from the perspectives of a sample of service-providers with a role in sexual health-care delivery. Design: Qualitative methodological strategy. Setting: Service-delivery sites at urban and rural locations in Ireland. Method: A total of 22 service-providers were interviewed in depth, and data were analysed using a qualitative analytical strategy resembling modified analytical induction. Findings: Participants proffered their perceptions and examples of their practices of sex education in relation to the following themes: (1) acknowledging the multi-dimensional nature of sexual health in the case of young people in care; (2) personal and emotional development education to address poor self-esteem, emotional disconnectedness and an inability to recognise and express emotions; (3) social skills' education as part of a repertoire of competencies needed to negotiate relationships and safer sex; (4) the application of positive social skills embedded in everyday social situations; and (5) factual sexuality education. Conclusion: Insights into service-providers' perceptions of the multi-dimensional nature of the sexual health needs of young people in state care, and the ways in which these service-providers justified their practice make visible the complex character of sex education and the degree of skill required to deliver it to those in state care.